2001
DOI: 10.1080/02652030117740
|View full text |Cite
|
Sign up to set email alerts
|

Presence of ochratoxin A in human milk in relation to dietary intake

Abstract: Individual and geographical variations in ochratoxin A (OA) levels in human blood and milk samples may be due to differences in dietary habits. The purpose of this study was to examine the relationship between OA contamination of human milk and dietary intake. Human milk samples were collected from 80 Norwegian women. The usual food intake during the last year was recorded using a quantitative food frequency questionnaire. The concentration of OA in the human milk was determined by HPLC (detection limit 10 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Of note, cereals based foods are the major contributors to human exposure to OTA, accounting for 50% to the mean European dietary intake [10], whereas pork meat is the most important dietary source of OTA among animal products [20]. These findings are in overall agreement with previous observations by Turconi et al [21], as specifically concerns bread, and with Skaug et al [22,23] for what regards cereals based foods and pork products. The possibility that other food groups, such as alcoholic beverages, can trigger the OTA presence in human mature milk is intriguing, however, our data do not allow definitive conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, cereals based foods are the major contributors to human exposure to OTA, accounting for 50% to the mean European dietary intake [10], whereas pork meat is the most important dietary source of OTA among animal products [20]. These findings are in overall agreement with previous observations by Turconi et al [21], as specifically concerns bread, and with Skaug et al [22,23] for what regards cereals based foods and pork products. The possibility that other food groups, such as alcoholic beverages, can trigger the OTA presence in human mature milk is intriguing, however, our data do not allow definitive conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…Rosner et al (2000) could not detect OTA in 27 samples of human milk (<0.06 ng ml À1 ). A study in Norway, where 17/80 samples of human milk contained OTA in the range 0.01-0.182 ng ml À1 , showed that women with a high intake of liver paste and cakes were significantly more likely to have OTA in their milk (Skaug et al 2001). Intake of juice (all kinds) was also a significant risk factor for OTA in the milk.…”
Section: Ochratoxin a In Human Milkmentioning
confidence: 99%
“…It has recently been demonstrated that OTA is present in spores and airborne dust (109)(110). A study conducted of three dairy farms in Norway (110) showed OTA in airborne dust ranging between 0.2 µg kg -1 and 70 µg kg -1 , with an average level of 27.5 µg kg -1 .…”
Section: Exposure Through Inhalationmentioning
confidence: 99%